2017
DOI: 10.1371/journal.pone.0182732
|View full text |Cite
|
Sign up to set email alerts
|

Dextran sodium sulfate (DSS) induces necrotizing enterocolitis-like lesions in neonatal mice

Abstract: BackgroundNecrotizing enterocolitis (NEC) is an inflammatory bowel disease of preterm human newborns with yet unresolved etiology. An established neonatal murine model for NEC employs oral administration of lipopolysaccharides (LPS) combined with hypoxia/hypothermia. In adult mice, feeding dextran sodium sulfate (DSS) represents a well-established model for experimental inflammatory bowel disease. Here we investigated the effect of DSS administration on the neonatal murine intestine in comparison with the esta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
33
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 42 publications
3
33
0
Order By: Relevance
“…71 Sangild et al showed that with a single stress factor alone, formula feeding of a human infant formula, 57% of piglets presented with clinical and histopathological signs of NEC, while piglets fed colostrum had a reduction in severity of NEC as well as in the adverse effects of feeding. 65 Of note in their study was the demonstration that NEC-like intestinal inflammation occurred after oral colostrum eating, without exposure to hypoxic or hypothermic insults. 65 Their group has also validated this model of NEC induction by confirming release of IL-6.…”
Section: Animal Models Of Necmentioning
confidence: 97%
See 3 more Smart Citations
“…71 Sangild et al showed that with a single stress factor alone, formula feeding of a human infant formula, 57% of piglets presented with clinical and histopathological signs of NEC, while piglets fed colostrum had a reduction in severity of NEC as well as in the adverse effects of feeding. 65 Of note in their study was the demonstration that NEC-like intestinal inflammation occurred after oral colostrum eating, without exposure to hypoxic or hypothermic insults. 65 Their group has also validated this model of NEC induction by confirming release of IL-6.…”
Section: Animal Models Of Necmentioning
confidence: 97%
“…65 Of note in their study was the demonstration that NEC-like intestinal inflammation occurred after oral colostrum eating, without exposure to hypoxic or hypothermic insults. 65 Their group has also validated this model of NEC induction by confirming release of IL-6. 72 Other investigators have used the newborn piglet model to show the role of reactive oxygen species in NEC, 73 gastric intramural pH monitoring in NEC, 74 attenuation of T cell-mediated mucosal immunity in NEC, 75 and the role of PAF in NEC.…”
Section: Animal Models Of Necmentioning
confidence: 97%
See 2 more Smart Citations
“…3 Acute and chronic inflammation, colonic adenocarcinoma, and necrotizing enterocolitis models have been reported by variations on dosing, inclusion of azomethane, and animal age, respectively. 4 In addition, the effectiveness of the DSS model depends on the strain and colony of mice used, as well as the DSS MW. As DSS is a polysaccharide, its MW can vary according to the number of monosaccharides attached, modifying its pharmacokinetics.…”
Section: Introductionmentioning
confidence: 99%